Walker V. Personius correspondence - Personius, Walker V., 1836-1914.
ALsS (1861 October 5-December 13; Camp Lesley, Washington, D.C.) from Personius during his service with the 50th New York Engineers to his parents documenting company activities and camp life. He describes Washington, D.C., its public buildings, and northern Virginia; expresses his hope that the war will end slavery; and discusses the construction of workshops and a road. Includes two covers, one with a picture of George Washington.
Union Army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army -- Military life; United States. -- Army. -- New York Engineers Regiment, 50th (1861-1865); Public buildings -- Washington (D.C.); Slavery -- United States; United States -- History -- Civil War, 1861-1865 -- Engineering and construction; Virginia -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Soldiers